2011
DOI: 10.1111/j.1530-0277.2011.01476.x
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Deep Gray Matter Volume Reductions in Children and Adolescents with Fetal Alcohol Spectrum Disorders

Abstract: Significant, but variable, volume reductions throughout the deep gray matter are observed over a wide age range of 6 to 17 years in FASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
121
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(135 citation statements)
references
References 55 publications
12
121
1
Order By: Relevance
“…Additional studies found the hippocampi to have smaller volumes in proportion to overall brain volume reduction (27,48). Basal ganglia volume reductions in alcohol-exposed children in comparison with their non-exposed peers have been reported by a number of authors (16,26,33,40,42,46,48,76). Alcohol exposure effects on the caudate have been most frequently cited (16,26,33,40,42,46,48,76), but also discrete changes in the globus pallidus (42,48,54), putamen (42,46,48,54,76) or the lenticular nucleus as a whole (40).…”
Section: Discussionmentioning
confidence: 85%
“…Additional studies found the hippocampi to have smaller volumes in proportion to overall brain volume reduction (27,48). Basal ganglia volume reductions in alcohol-exposed children in comparison with their non-exposed peers have been reported by a number of authors (16,26,33,40,42,46,48,76). Alcohol exposure effects on the caudate have been most frequently cited (16,26,33,40,42,46,48,76), but also discrete changes in the globus pallidus (42,48,54), putamen (42,46,48,54,76) or the lenticular nucleus as a whole (40).…”
Section: Discussionmentioning
confidence: 85%
“…Diffusion tensor imaging techniques have revealed that white matter appears especially vulnerable to alcohol, with reduced microstructural integrity found in children with PAE in areas associated with processing speed, nonverbal ability, and executive functioning (for a review, see . The corpus callosum, the largest white fiber tract, and other commissural and temporal connections are all sensitive to the teratogenic influences of alcohol (Lebel et al, 2008) as are the deep gray matter structures (Nardelli, Lebel, Rasmussen, Andrew, & Beaulieu, 2011). Additionally, there is nascent evidence of reduced functional connectivity in the brains of individuals with PAE .…”
Section: Neurocognitive Profilementioning
confidence: 98%
“…In children and adolescents with FASD, large volume reductions were seen in the cerebrum [45], cerebellum ( Fig.3 [18]. Volume reduction and structural dysmorphology co-occurred in the case of the cerebellar vermis [49], but structural dysmorphology and asymmetry were present in the absence of volume changes in the case of the hippocampus and caudate nucleus [55;56].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The density of postsynaptic dopamine receptors and the level of presynaptic dopamine synthesis are finely regulated to maintain their balance [154]. The macaque PAE studies used well-established radiotracers, 18 F-Fallypride [154] and 11 C-SCH23390 [155], to target the dopamine receptor D2 and D1, respectively. The macaques received a moderate concentration of ethanol (6% v/v consumed voluntarily daily, producing an average blood alcohol concentration of 20-50 mg/dl 60 min after consumption), during (i) early gestation only (gestational day, GD, 0-50, equivalent to the first trimester in humans) [154], (ii) late gestation only (GD50-135) [154], or (iii) throughout gestation [154;155].…”
Section: Non-human Primate Pet Studiesmentioning
confidence: 99%